A Comparative Study on Syntactic Morphological Similarities and Differences between Korean and Persian Languages - Farhad Khabazian (International Journal of Practical and Pedagogical Issues in English Education)
This research aimed to compare Korean and Persian languages both in syntactic and morphological phases. Based on research questions, this research used qualitative approach to figure out and explore the specific detailed information about the topic. The present article seeks to briefly compare some of main similarities and differences of target languages. The researcher used previous studies and researches about each of Korean and Persian syntactic morphological features. In this qualitative case study a total of 22 researches and books were used to collect data about syntactic morphological features of Korean and Persian languages in this research. No research, to date, compared these linguistic elements of Korean and Persian. In general, there are some similarities and differences between syntax and morphology of these Asian languages. A comparative study on these structures is useful because it can help Iranian KFL learners to enhance the process of learning Korean language.